Construction modeling and parameter optimization of multi-step horizontal energy storage salt caverns. (15th July 2020) - Li, Jinlong; Shi, Xilin; Zhang, Shuai
Abstract: A multi-step horizontal leaching method can be used to efficiently construct energy storage salt caverns. However, the modeling and control of a multi-step horizontal cavern are complicated and have been investigated little, resulting in many collapses of such caverns. To predict the 3-D development of a horizontal salt cavern during construction, a numerical model is proposed based on a composite structural mesh. The salt dissolution rate is introduced as being related to the brine concentration. The flow/concentration fields are dynamically divided into four subareas. Their governing equations are derived based on mass and volume conservation. The accumulation and re-distribution of the insoluble substances are considered. A C++ program is developed for model implementation. The feasibility and accuracy of the model are verified by comparisons with data in published literature. A series of simulations have been conducted for technological parameter optimization. Results show that using a larger borehole length increases cavern capacity. Using a larger step distance increases the construction control but decreases the cavern capacity. Using a larger flow rate increases construction efficiency but decreases the energy-saving coefficient and construction control. A long borehole length, a medium step distance and a variable flow rate are suggested for horizontal cavern construction. Highlights: A model is presented for the construction of a multi-step horizontal salt cavern. A composite structural mesh is proposed to describe the boundary movements. A dynamic zoning model is proposed for the flow/concentration field. A series of simulations are conducted for parameter optimization. A long borehole length, medium step distance and dynamic flow rate are suggested.